[Goðafoss in North Iceland] - Streng, Evelyn Fiedler (1975)
Photograph of Goðafoss Waterfall. Grey water sits at the bottom and the top of the falls, broken up by brown rocks. Green and grey, flat mountains sit in the background below grey clouds. White mist shoots up from the three waterfalls to the left.